Strain-engineered optical gain in GaAs0.4Sb0.6/InP0.9Sb0.1 type-II heterostructures for near-infrared nano-optoelectronics - Amit Rathi; Priya Chaudhary; Amit Kumar Goyal (Results in Physics)
This study investigates the enhancement of optical gain in type-II GaAs0.4Sb0.6/InP0.6Sb0.1 nanoscale heterostructures under externally applied uniaxial strain for potential applications in near-infrared optoelectronic devices. Using the 6 × 6 Luttinger-Kohn model within the k·p perturbation framework, we analyze the band structure, envelope wavefunctions, and transition matrix elements at 300 K. Without strain, an optical gain of 13,631 cm−1 is observed at an injected carrier concentration of 5 × 1012 cm−2. Applying external strain (2, 4, and 6 GPa) along the [100] and [001] crystallographic directions significantly enhance the optical gain within the infrared spectral range. Temperature- and strain-dependent gain simulations in x-polarization further confirm the heterostructure’s efficacy in supporting near-infrared emission. These results highlight the potential of the GaAsSb/InPSb heterostructure as a promising candidate for strain-tunable, high-performance nano-optoelectronic and laser applications.